ACCOMMODATION, RESISTANCE AND DIVIDED COMMUNITY: STUDY OF THE DYNAMICS OF OFFSHORE TIN MINING CONFLICT BETWEEN THE FISHERMEN OF THE COASTAL AREA AND COMPANIES IN BANGKA ISLAND - Sulista, Sulista; Ibrahim, Ibrahim; Pratama, Sandy (PEOPLE: International Journal of Social Sciences, 2019)
During fifteen years, the tin mining in Bangka Island has becoming more intensive and hold by the mining business licence holders. Although already has permit, it doesn’t mean that the mining activity can be undergo for it is also the place for the local fishermen doing their business. The purpose of this study is to obtain the conflict dynamics and also the motive of the community’s attitude toward the mining activity. The research methodology was carried out by focus group discussions with affected community groups and in-depth interviews with local leaders and village/urban village government officials which were further analyzed exploratively. The results of the analysis show that there are 3 models of community response to tin mining aggression in the territorial waters of Bangka, which are accommodating, rejecting with a strong pattern of resistance, and multiple attitudes towards people who are divided in their attitudes and interests.